Energy efficient hybrid routing protocol for Wireless Sensor Networks Using AI Technique - Kumar Gautam, Amit; Yadav, Ravi (EAI Endorsed Transactions on Scalable Information Systems, 2021)
Wireless sensor networks (WSNs) are frequently used in various critical sectors such as monitoring of nuclear power plants, habitat monitoring, precision agriculture, internet of things (IoT), industrial management, etc. Various challenges such as the limited resources in sensor nodes can bound their usefulness. In the critical application of WSN, energy conservation is a major problem in the routing process to extend network life. Clustering is one of the promising techniques for efficient utilization of energy in the network. Our proposed method is using a hybrid routing protocol for efficient utilization of energy in the network. In our hybrid clustering mechanism, Fuzzy Logics is used for the selection of cluster heads based on distance, noise, and residual energy as parameters of sensor nodes. The simulation results show that our proposed method has a 43.57% better stability period than the SEP protocol. The simulation results also show that the hybrid routing protocol has 15 % better network lifetime than SEP Protocol.
Keywords: Routing; Region-based; Fuzzy logic; Residual energy